Embryonic transcriptome unravels mechanisms and pathways underlying embryonic development with respect to muscle growth, egg production, and plumage formation in native and broiler chickens - Kanakachari, M.; Ashwini, R.; Chatterjee, R. N.; Bhattacharya, T. K. (Frontiers in Genetics, 2022)
Muscle development, egg production and plumage colours are different between native and broiler chicken. The study was designed to investigate why improved Aseel (PD4) is colorful, stronger and grew slowly compared with the control broiler (CB); microarray was conducted with the 7th-day embryo (7EB) and 18th-day thigh muscle (18TM) of improved Aseel and broiler, respectively. Also, we have selected 24 Gallus gallus candidate reference genes from NCBI, and total RNA was isolated from the broiler, improved Aseel embryo tissues, and studied their expression profiles by real-time quantitative PCR (qPCR). Further, microarray data was validated with qPCR using improved Aseel and broiler embryo tissues. In the differential transcripts screening, all the transcripts obtained by microarray of slow and fast growth groups were screened by fold change ≥1 and false discovery rate (FDR) <0.05. In total, 19022 transcripts were differentially expressed between the 7EB and 18TM of PD4 compared to the CB. Further analysis showed that a high number of transcripts are differentially regulated in the 7EB of PD4 (15382), and fewer transcripts were differentially regulated (3640) in the 18TM of PD4 compared to the CB. On the 7th and 18th-day PD4 embryo, 10127, 2102, 5255, and 1538 transcripts were up and down-regulated, respectively. The commonly up and down-regulated transcripts were 545 and 381 between the 7th and 18th-day of embryos. Additionally, the best housekeeping genes were also identified. Further, validated the differentially expressed genes (DEGs) related to muscle growth, myostatin signaling and development, fatty acid metabolism genes in PD4 and CB embryo tissues by qPCR, and the results correlated with microarray expression data. Our study identified DEGs that regulate myostatin signaling and differentiation pathway, glycolysis and gluconeogenesis, fatty acid metabolism, Jak-STAT, mTOR, and TGF-β signaling pathways, tryptophan metabolism, PI3K-Akt signaling pathways in PD4. The results revealed that the gene expression architecture is present in the improved Aseel exhibiting embryo growth that will help to improve muscle development, differentiation, egg production, protein synthesis, and plumage formation in native chicken. Our findings may be used as a model for improving the growth in Aseel as well as optimizing the growth in the broiler.